Taxation of Corporations and Their Impact on Economic Growth: The Case of EU Countries - Baranová Veronika; Janíčková Lenka (Journal of Competitiveness, 2012)
One of the most debated questions in economy is the relationship between tax rates and economic growth. Especially taxation of corporations has great importance because a corporate tax base is quite a mobile factor of production and simultaneously the tax competition is currently still tougher due to required economic development particularly in the context of the economic crisis. Based on the available literature, we can deductively derive and suppose an inverse relationship between tax burden and economic growth; on the other side, the degree of correlation is not so obvious. The aim of this article is to verify the expected negative relationship between corporate taxation and long-term economic growth in the sample countries. This analysis is based on the neoclassical growth model extended with human capital. Furthermore, the model associated with the variable reflecting the different possibilities to measure the tax burden on corporations, especially tax quota separated on income taxation of corporations, the implicit tax rate on capital and effective tax rates secured by micro-forward looking methods. The default is a panel regression methodology and related methods of data analysis. The sample consists of EU member states. The reference periods are the annual frequencies in the time frame 1998 - 2010.